Factors associated with condom use in women of a testing and advice center for STD/AIDS of Bahia, Brazil - Silva, Artur Alves da; Viana, Acássio dos Santos Amorim; Rezende, Raisa Evaly Alves de; Ferreira, Caroline de Oliveira; Davoglio, Rosane Silvia (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: The feminization process of the human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) infection in Brazil is evidenced by the expressive increase in the number of infected women and by mortality rates, which is increasing in females, contrary to what occurs among men. Despite the diffusion of condoms, consistent use is still considered low, even in relations with non-regular partners. Objective: To investigate factors associated with the use of condoms with non-regular partners, in women users of a Testing and Counseling Center for sexually transmitted disease (STD)/AIDS of Bahia, from 2006 to 2012. Methods: This is a transversal observational analytical study. Secondary data of 790 women users of a Testing and Counseling Center, obtained from forms and clinical records, were used. Statistical analysis, crude and adjusted, used the prevalence ratio as the measure of association and a 95% confidence interval. Results: The consistent use of condom in relations with non-regular partners was low (27.97%). The main reasons appointed to justify the absence of use were not liking it (35.71%) and difficulty in negotiating with the partner (21.22%). The outcome was associated statistically to the absence of use of condom in the last relation with a regular partner and to the age of first sexual relation lower than 16 years. Conclusion: The findings contribute to the understanding of the behavior of women in relationships with non-regular partners and provide a base in planning coping actions against the diseases resulting from unprotected sex, both in specialized care and in the primary health care network.